Direct observation of the influence of the As-Fe-As angle on the T c of superconducting SmFeAsO1-xFx - Garbarino, G. (2011)
The electrical resistivity, crystalline structure, and electronic properties calculated from the experimentally measured atomic positions of the compound SmFeAsO0.81F0.19 have been studied up to pressures ∼20 GPa. The correlation between the pressure dependence of the superconducting transition temperature (Tc) and crystallographic parameters on the same sample shows clearly that a regular FeAs4 tetrahedron maximizes Tc through optimization of carrier transfer to the FeAs planes as indicated by the evolution of the electronic band structures.